Soil dataset from poplar cultivation sites in northern Italy plains - Daniele Rizza; Roberto Barbetti; Pier Mario Chiarabaglio; Alessandro Rocci (Annals of Silvicultural Research)
The data pertains to georeferenced soil samples collected from poplar plantations situated in the plains of northern Italy between 1994 and 1996 and targeted areas with poplar plantations that were at least five years old in 1994.